Biomechanical Comparison Considering Risk Of Backpack On Lumbosacral Joint Among Primary Student : During Standing And Climbing Stairs - Mohd Hassan, Nur Alya Syaherah (2020)
Backpack represent the most widely used method to carry the school items among children and teenagers with percentages up to 90% and more. Excessive load of backpack may lead to various musculoskeletal disorder among the primary student. Heavy backpack is commonly associated with higher prevalence of low back pain among the primary student. The recommended weight of schoolbags are 10% of their body weight. This study was conducted to assess the effect of the weight of the backpack towards the lumbosacral joint (L5/S1) of primary student in three different condition which are standing with no load, standing with a backpack and climbing the stairs with a backpack. A total of 10 respondents from the primary school students will be involved during the survey of this study. A set of questionnaires of their psychophysical experience will be distributed among the respondents. The participants were required to perform three activity which are standing without a load on their back, standing while holding a backpack and climbing the stairs while carrying the backpack. This three activity will be recorded by using a digital camera. ImageJ Software was used to measure the joint angles and gait parameters. Based on the data measured by the software, a static analysis will be applied to calculate the torque and force for the trunk musle, compressive and a shear force acting on the lumbosacral joint. The trunk flexion angle increased from standing with no load to standing while carrying a backpack to climbing the stairs while carrying a backpack. The sum of the magnitude of external torque and the resultant joint reaction forces increased from no load to carry a backpack and climbing the stairs.